Nosological profile of dermatological diseases in primary health care and dermatology secondary care in Florianópolis (2016-2017), - Iago Gonçalves Ferreira; Dannielle Fernandes Godoi; Elaine Regina Perugini (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background Dermatology encompasses the management of many disorders of the skin and cutaneous appendages, making the analysis of epidemiological profiles relevant for health planning. Objective The study aims to describe the nosological profile of dermatological diseases in Florianopolis, analyzing the interrelation among the primary health care and dermatology services, from January 2016 to December 2017. Method Descriptive study from records of medical visits from the primary health care and dermatology services, as well as records of reports issued by the teledermatology service. Results In primary health care, from 55,265 medical visits - 28,546 in 2016 and 26,719 in 2017, there was a higher prevalence of "Atopic dermatitis" (6.38%), "other disorders of skin and subcutaneous tissue" (5.10%), and "Scabies" (4.55%). In dermatology secondary care, from 19,964 visits - 10,068 in 2016 and 9626 in 2017, the most prevalent diagnoses were "Other malignant neoplasms of the skin" (14.75%) and "Skin changes due to chronic exposure to nonionizing radiation" (10.20%). Study limitations Some dermatological consultations in primary health care may have been under-registered due to the attribution of non-specific or overly broad diagnoses. Conclusion This study presents different nosological profiles of skin diseases in primary health care and dermatology secondary care, reinforcing the importance of primary health care's role in the management of less complex conditions, referring more complex cases that require more specialized experience to dermatology services..